Soil parameters affecting longleaf pine (Pinus palustris) site quality in east Texas - Brian P. Oswald; Ryan Svehla; Kenneth W. Farrish (Forestry Research)
The decline since European colonization in longleaf pine (Pinus palustris Mill.) within its range in the southeastern United States, attributed to factors including both site conversion and fire exclusion has spurred interest in the re-establishment of the species. Land that originally supported longleaf pine in the southeastern United States has often been converted for agricultural use, loblolly pine (Pinus taeda Mill.) plantations, and urban development. Longleaf pine was found on a wide range of soil properties due to frequent fires which kept many competing species suppressed; fire has often been excluded due to human health, safety, and liability concerns. Longleaf pine ecosystem restoration efforts might be best focused on soils that have characteristics that naturally restrain herbaceous and hardwood competition. Properties of three soil series in east Texas that historically or are currently supporting longleaf pine ecosystems were evaluated. Analysis of Variance, Principal Component Analysis, and regression techniques were used to compare soil properties; while all three soils historically supported longleaf pine, they vary in texture, depth to argillic horizons, nutrient availability, available water capacity, and other parameters which are likely related to site quality, as measured by site index. Longleaf pine site index is influenced by depth to E and the first argillic B horizons, B horizon texture and nutrients. B horizon physical and chemical variables appear to be the most influential for longleaf pine site index on these sites, and should be considered when evaluating potential sites for longleaf pine restoration efforts.